Quality-of-Life Outcomes of Older Adults with Severe Disabilities. (December 2019) - Friedman, Carli
People with disabilities who age may have unique experiences and face different challenges than people without disabilities who acquire disabilities as they age. These unique challenges may be especially pertinent for people with severe disabilities who already face disparities in quality of life. Yet, there is little research specifically about the quality of life of older adults with severe disabilities, a population that has continued to grow due to advances in medicine and social supports. This study's aim was to explore quality-of-life outcomes of older adults with severe disabilities. We analyzed Personal Outcome Measures® data from 800 people with severe disabilities aged 55 years old and older. Findings revealed most older adults with severe disabilities had less than half of the quality-of-life outcomes present. Specifically, we found that while most older adults with severe disabilities were healthy, safe, and free from abuse and neglect, the overwhelming majority were lacking in community integration, relationships, choice, and opportunities. Our findings suggest the lack of quality-of-life outcomes among older adults with severe disabilities were largely attributed to an absence of supports. When older adults with severe disabilities received individualized organizational supports, they had better quality of life.